Farnesoid X receptor promotes renal ischaemia‐reperfusion injury by inducing tubular epithelial cell apoptosis. (16th February 2021) - Xu, Yao; Li, Dawei; Wu, Jiajin; Zhang, Minfang; Shao, Xinghua; Xu, Longmei; Tang, Lumin; Zhu, Minyan; Ni, Zhaohui; Zhang, Ming; Mou, Shan
Abstract: Purpose: We investigated the role of farnesoid X receptor (FXR), a ligand‐dependent transcription factor, in renal ischaemia‐reperfusion (I/R) injury. Materials and Methods: We performed unilateral renal I/R model in FXR knockout ( Fxr −/− ) and wild‐type (WT) mice in vivo and a hypoxia‐reoxygenation (H/R) model in vitro. The pathways by which FXR induces apoptosis were detected using a proteome profiler array. The effects of FXR on apoptosis were evaluated using immunoblotting, TUNEL assays and flow cytometry. Results: Compared with WT mice, Fxr −/− mice showed improved renal function and reduced tubular injury scores and apoptosis. Consistent with the in vivo results, the silencing of FXR decreased the number of apoptotic HK‐2 cells after H/R, while FXR overexpression aggravated apoptosis. Notably, bone marrow transplantation (BMT) and immunohistochemistry experiments revealed the involvement of FXR in the tubular epithelium rather than in inflammatory cells. Furthermore, in vivo and in vitro studies demonstrated that FXR deficiency increased phosphorylated Bcl‐2 agonist of cell death (p‐Bad) expression levels and the ratio of Bcl‐2/Bcl‐xL to Bax expression in the kidney. Treatment with wortmannin, which reduced p‐Bad expression, inhibited the effects of FXR deficiency and eliminated the tolerance of Fxr −/− mouse kidneys to I/R injury. Conclusions: These results established the pivotal importance of FXR inactivation in tubular epithelial cells after I/R injury. FXR may promote the apoptosis of renal tubular epithelial cells by inhibiting PI3k/Akt‐mediated Bad phosphorylation to cause renal I/R damage. Abstract : We found the important role of FXR in survival signalling and death regulation in renal tubular epithelium, providing support for FXR as a vital regulator of renal biology. It suggested that FXR participated in renal I/R injury and could be a therapeutic target for AKI.